2022
DOI: 10.1108/compel-09-2021-0358
|View full text |Cite
|
Sign up to set email alerts
|

Fault detection and classification of DC microgrid based on VMD

Abstract: Purpose This paper aims to present a new fault detection and classification scheme of both DC faults and AC faults on a DC microgrid network. Design/methodology/approach To achieve reliable protection, the derivative of DC current signal is decomposed into several intrinsic modes using variational mode decomposition (VMD), which are then used as inputs to the Hilbert–Haung transform technique to obtain the instantaneous amplitude and frequency of the decomposed modes of the signal. A weighted Kurtosis index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…1–11), given in Table 4. Similarly, PP and ARC fault detection times are 1.2 ms and 10 ms, which are also lower as compared to detection times in Barik (2023, pp. 302–322) and Shamsoddini et al (2020, pp.…”
Section: Results Analysismentioning
confidence: 82%
See 2 more Smart Citations
“…1–11), given in Table 4. Similarly, PP and ARC fault detection times are 1.2 ms and 10 ms, which are also lower as compared to detection times in Barik (2023, pp. 302–322) and Shamsoddini et al (2020, pp.…”
Section: Results Analysismentioning
confidence: 82%
“…In proposed fault detection method, three types of fault detection like PG fault detection, PP fault detection and ARC fault detection have been carried out. It is observed that the detection time for PG fault is 2.4 ms, which is less as compared to the detection time in Barik (2023, pp. 302–322) and Shamsoddini et al (2020, pp.…”
Section: Results Analysismentioning
confidence: 85%
See 1 more Smart Citation